MODULATION OF MUTANT SUPEROXIDE DISMUTASE 1 AGGREGATION BY CO-EXPRESSION OF WILD-TYPE ENZYME - Prudencio, Mercedes (2008)
Mutations in superoxide dismutase 1 (SOD1, EC 1.15.1.1) cause familial amyotrophic lateral sclerosis (fALS); with aggregated forms of mutant protein accumulating in spinal cord tissues of transgenic mouse models and human patients. Mice over-expressing wild-type human SOD1 (WT hSOD1) do not develop ALS-like disease, but co-expression of WT enzyme at high levels with mutant SOD1 accelerates the onset of motor neuron disease compared to mice expressing mutant hSOD1 alone. Spinal cords of mice expressing both proteins contain aggregated forms of mutant protein and, in some cases, evidence of co-aggregation of WT hSOD1 enzyme. In the present study, we used a cell culture model of mutant SOD1 aggregation to examine how the presence of WT SOD1 affects mutant protein aggregation, finding that co-expression of WT SOD1, human (hSOD1) or mouse (mSOD1), delayed the formation of mutant hSOD1 aggregates; in essence appearing to slow the aggregation rate. In some combinations of WT and mutant hSOD1 co-expression, the aggregates that did eventually form appeared to contain WT hSOD1 protein. However, WT mSOD1 did not co-aggregate with mutant hSOD1 despite displaying a similar ability to slow mutant hSOD1 aggregation. Together, these studies indicate that WT SOD1 (human or mouse), when expressed at levels equivalent to the mutant protein, modulates aggregation of FALS-mutant hSOD1.